Along the Domestic-Foreign Frontier; Exploring Governance in a Turbulent World - Rosenau, James N (New York, 1997)
James N. Rosenau explores the enormous changes that are currently transforming world affairs. He argues that the dynamics of economic globalization, new technologies, and evolving global norms are clashing with equally powerful localizing dynamics. The resulting encounters between diverse interests and actors are rendering domestic and foreign affairs ever more porous and creating a political space, designated as the "Frontier," wherein the quest for control in world politics is joined. He contends that it is along the Frontier, and not in the international arena, that issues are contested and the course of events configured.
Keywords: International Relations